iPSC-Derived Pancreatic Progenitors Lacking FOXA2 Reveal Alterations in miRNA Expression Targeting Key Pancreatic Genes - Noura Aldous (15429873) (2023)
Poster by Noura Aldous, Ahmed Elsayed, Nehad Alajez, and Essam M. Abdelalim (Hamad Bin Khalifa University) Background: Generation of pancreatic beta cells from human pluripotent stem cells (hPSCs) is a promising approach for studying diabetes pathogenesis and transplantation therapy. Our recent study showed that FOXA2 is crucial for human alpha and beta cell development during pancreatic islet differentiation. However, whether miRNAs are regulated by FOXA2 or not is largely unknown. Objective: In this report, we aimed to capture the dysregulated miRNAs associated with the absence of FOXA2 and identify their pancreatic-specific target genes in the iPSC-derived pancreatic progenitors (iPSC-PPs).  Methods: Two different FOXA2 knockout (FOXA2–/–) hiPSC lines were generated using CRISPR/Cas9. FOXA2–/–hiPSCs and their isogenic controls were differentiated into PPs in vitro using our protocol. PPs generated from FOXA2–/–hiPSCs and WT controls were exposed to RNA-sequencing and miRNA-sequencing. Gene ontology (GO) and KEGG pathways analyses were performed on the differentially expressed genes (DEGs). For differentially expressed miRNAs, a fold-change of >2 with a P-value <0.05 was used as a cutoff to determine the differentially expressed miRNAs in FOXA2–/–hiPSCs versus WT-hiPSCs. Pathway analysis and miRNA target genes identification was performed using Ingenuity Pathway Analysis (IPA) software. RT-qPCR was performed for validating selected DEGs and miRNAs.  Results: Transcriptome analysis on FOXA2–/–PPs compared to WT-PPs revealed 1628 down-regulated (Log2 FC < −1.0, p < 0.05) and 769 up-regulated (Log2 FC > 1.0, p < 0.05) DEGs. Several important transcription factors (TFs) required for pancreatic islet development and function were significantly downregulated in FOXA2–/–PPs such as PDX1, NKX6.1, SOX9, PAX4, GATA6, NEUROG3, NEUROD1, and PTF1A, which were also validated by RT-qPCR. Furthermore, genes associated with MODY, pancreatic development, Notch and WNT signaling pathways were downregulated, while glucose and cholesterol homeostasis associated genes were upregulated. miRNA-seq data analysis on FOXA2–/–PPs showed 107 downregulated (Log2 FC < −1.0, p < 0.05) and 111 upregulated (Log2 FC > 1.0, p < 0.05) differentially expressed miRNAs. Integrating miRNA and mRNA profiling using IPA showed that 190 miRNAs target 2654 mRNAs. Our analysis showed that the upregulated miRNAs (miR-92a-2-5p, miR-92b-5p, and miR-184) targeted both FOXA2 and NKX6.1, while miR-124-3p targeted multiple important pancreatic TFs including FOXA2, NGN3, NEUROD1, GATA6, SOX9, INSM1, and RFX6. miR-291a-3p is another miRNA that was found to have several target genes including NGN3, GLIS3, ARX, ONECUT1, and NEUROD1. Multiple upregulated miRNAs targeted key pancreatic TFs in FOXA2–/–PPs including NKX6.1, NEUROD1, ONECUT1, NGN3, PTF1A, GATA6, GATA4, RFX6, PDX1, and PAX4. miR-122-5p, miR-184, miR-194-5p, miR-373-3p, miR-885-5p, and miR-371a-3p were validated for upregulated miRNAs, while miR-493-3p was validated for downregulated miRNAs. Conclusion: These findings indicate that the expression of FOXA2 during pancreatic islet development is crucial in maintaining the normal expression of the key miRNAs that target pancreatic endocrine TFs.